Normotensive and hypertensive Immunoglobulin a nephropathy with ischemic renal injury: clinicopathological characteristics and prognosis - Yongli Wang (Taylor & Francis Group, 2021)
Objectives This study aimed to investigate the clinicopathological characteristics and prognosis of normotensive and hypertensive IgAN patients with ischemic renal injury. Methods A total of 344 cases of IgAN with ischemic renal injury were included in the study, including 99 normotensive IgAN patients (28.8%) and 245 hypertensive IgAN patients (71.2%). In addition, 467 IgAN patients without ischemic renal injury were included as controls, including 205 normotensive patients and 262 hypertensive patients. Clinicopathological and prognostic data were collected and analyzed. Results Compared with patients without ischemic renal injury, IgAN patients with ischemic renal injury displayed a higher proportion of hypertention, a higher proportion of ischemic glomerulosclerosis, tubular atrophy/interstitial fibrosis and vascular lesions (all p < .05). There was no significant difference in cumulative survival between the normotensive IgAN patients groups (Log-rank χ2 = 0.479; p = .489). Furthermore, ischemic renal injury was not a risk factor for end-point events in normotensive IgAN patients (HR = 1.103; 95% CI: 0.279–4.365; p = .889). There was lower cumulative survival in hypertensive IgAN patients with ischemic renal injury (Log-rank χ2 = 11.352, p = .001). Moreover, ischemic renal injury was a risk factor for end-point events in hypertensive IgAN patients (HR = 1.889; 95% CI: 1.124–3.178; p = .016). Conclusions Ischemic renal injury can occur in normotensive IgAN patients. Although the pathological changes may not affect the long-term prognosis of normotensive IgAN patients, the prognosis for hypertensive IgAN patients remains poor. Therefore, increased attention should be paid to the clinical management of ischemic lesions in hypertensive IgAN patients.